Working Memory for Sequences of Temporal Durations Reveals a Volatile Single-Item Store - Manohar, Sanjay G.; Husain, Masud (Frontiers in Psychology, 2016)
When a sequence is held in working memory, different items are retained with differing fidelity. Here we ask whether a sequence of brief time intervals that must be remembered show recency effects, similar to those observed in verbal and visuospatial working memory. It has been suggested that prioritising some items over others can be accounted for by a “focus of attention”, maintaining some items in a privileged state. We therefore also investigated whether such benefits are vulnerable to disruption by attention or expectation. Participants listened to sequences of one to five tones, of varying durations (200ms to 2s). Subsequently, the length of one of the tones in the sequence had to be reproduced by holding a key. The discrepancy between the reproduced and actual durations quantified the fidelity of memory for auditory durations. Recall precision decreased with the number of items that had to be remembered, and was better for the first and last items of sequences, in line with set-size and serial position effects seen in other modalities. To test whether attentional filtering demands might impair performance, an irrelevant variation in pitch was introduced in some blocks of trials. In those blocks, memory precision was worse for sequences that consisted of only one item, i.e. the smallest memory set size. Thus, when irrelevant information was present, the benefit of having only one item in memory is attenuated. Finally we examined whether expectation could interfere with memory. On half the trials, the number of items in the upcoming sequence was cued. When the number of items was known in advance, performance was paradoxically worse when the sequence consisted of only one item. Thus the benefit of having only one item to remember is stronger when it is unexpectedly the only item. Our results suggest that similar mechanisms are used to hold auditory time durations in working memory, as for visual or verbal stimuli. Further, solitary items were remembered better when more items were expected, but worse when irrelevant features were present. This suggests that the “privileged” state of one item in memory is particularly volatile and susceptible to interference.